Global access to clean water - Kallen, Stuart A., 1955- (Real-world STEM., 2018)
Explores the challenges faced by engineers and scientist as they work to ensure that clean water is available to everyone around the world. Highlights the current state of available clean water and examines potential solutions. Includes a diagram, resources for further information, and color photographs.